(untitled) (Quaestiones Disputatae: temas en debate, 2022)
Lately, the world has witnessed a series of scientific, political, social, etc. events that have been framed under the term “post-truth”. Contrary to what one might think, post-truth goes beyond the spread of fake news on social media. In reality, this phenomenon represents a breakdown in social relations and a strong mediatisation in the interaction of the subject with his or her environment. For this reason, this article seeks to articulate the notion of post-truth in a conceptual framework based on the postulates of Jean-François Lyotard, Gilles Lipovetsky, Jean Baudrillard, Guy Debord, among others. Thanks to the considerations of these thinkers on individualism, personalisation, hyper-consumption, seduction and narcissism, the reader will understand that post-truth is one of the major expressions of hyper-modernity and a cause and effect of the era in which we are living, namely hyper-modernity.